Morphological reproductive characteristics of testes and fertilization capacity of cryopreserved sperm after the Fukushima accident in raccoon (Procyon lotor). Issue 3 (18th January 2021) - Komatsu, Kazuki; Iwasaki, Tsugumi; Murata, Kosuke; Yamashiro, Hideaki; Goh, Valerie Swee Ting; Nakayama, Ryo; Fujishima, Yohei; Ono, Takumi; Kino, Yasushi; Simizu, Yoshinaka; Takahashi, Atsushi; Shinoda, Hisashi; et al.
Abstract: Since the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, we have established an archive system of livestock and wild animals from the surrounding ex‐evacuation zone. Wildlife within the alert zone have been exposed to low‐dose‐rate (LDR) radiation for a long continuous time. In this study, we analysed the morphological characteristics of the testes and in vitro fertilization (IVF) capacity of cryopreserved sperm of racoons from the ex‐evacuation zone of the FDNPP accident. The radioactivity of caesium‐137 ( 137 Cs) was measured by gamma‐ray spectrometry, and the measured radioactivity concentration was 300–6, 630 Bq/kg in the Fukushima raccoons. Notably, normal spermatogenesis was observed in the seminiferous tubules of the testes, with the germinal epithelium composed of a spermatogenic cell lineage with no evident ultrastructural alterations; freeze‐thawing sperm penetration ability was confirmed using the interspecific zona pellucida‐free mouse oocytes IVF assays. This study revealed that the chronic and LDR radiation exposure associated with the FDNPP accident had no adverse effect on the reproductive characteristics and functions of male raccoons.